2012
DOI: 10.1177/0269215512446093
|View full text |Cite
|
Sign up to set email alerts
|

Extension traction treatment for patients with discogenic lumbosacral radiculopathy: a randomized controlled trial

Abstract: The traction group receiving lumbar extension traction in addition to hot packs and interferential therapy had better effects than the control group with regard to pain, disability, H-reflex parameters and segmental intervertebral movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(114 citation statements)
references
References 36 publications
2
104
2
6
Order By: Relevance
“…This randomized controlled trial suggests that the addition of a novel cervical traction method (FCR H-reflex-based traction) to a multimodal treatment program in the form of physical pain relief methods (infrared, interferential therapy, and massage), muscle strengthening, and thoracic spine manipulation yields a significant additional benefit to disability, pain, nerve root function represented by the amplitude and latency of (53) 3 (69) 21 (51) b .005 NSAID Pre treatment 30 (42) 31 (41) 29 (43) .9 After 4 wk 22 (50) 10 (62) 14 (58) .04 At 1-y follow up 20 (52) 4 (68) 19 (53 The values are the mean (SD) for age, height, weight, and duration of pain. The patients could have received more than one treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This randomized controlled trial suggests that the addition of a novel cervical traction method (FCR H-reflex-based traction) to a multimodal treatment program in the form of physical pain relief methods (infrared, interferential therapy, and massage), muscle strengthening, and thoracic spine manipulation yields a significant additional benefit to disability, pain, nerve root function represented by the amplitude and latency of (53) 3 (69) 21 (51) b .005 NSAID Pre treatment 30 (42) 31 (41) 29 (43) .9 After 4 wk 22 (50) 10 (62) 14 (58) .04 At 1-y follow up 20 (52) 4 (68) 19 (53 The values are the mean (SD) for age, height, weight, and duration of pain. The patients could have received more than one treatment.…”
Section: Discussionmentioning
confidence: 99%
“…22 The positive 51 Several other related studies, while pertaining to lumbar area, have also highlighted the role of extension traction in improving the nerve root function and reducing pain. 52,53 The biomechanics of vascular system may be another possible explanation for the favorable results of extension position. It is postulated that the blood vessels of the dorsal and ventral roots will deform with postural changes.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of paralleled spine alignment improvements with reductions in pain and disability, versus no change in untreated control groups in pre-post clinical trials have been performed [18][19][20][21][22][23]. The demonstration in randomized clinical trials that only patient groups achieving lordosis and sagittal posture improvement (lumbar or cervical) achieve long-term improvements in various outcome measures versus comparative treatment groups not getting spine alignment improvement who experience regression in multiple outcome measures at follow-up have also been done [24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Today the evidence supporting the CBP approach to the correction of cervical lordosis and lumbar lordosis is substantial. There are now many randomized controlled clinical trials (RCT) documenting the reduction of anterior head translation [24,[28][29][30][31][32][33][34][35], as well as the increase in cervical lordosis [24,[28][29][30][31][32][33][34][35], and the increase in lumbar lordosis [25][26][27] in patients presenting with hypolordosis in each of these spinal areas. These trials have also demonstrated that the postural and spinal improvements are associated with improvements in various patient outcomes, including: pain, disability, quality of life, range of motion as well as specific physiological measures such as improved neurological central conduction times-the ability of the brain to communicate with the body.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic application of a stretching motion in scoliosis to increase flexibility may affect abdominal and pelvic muscles9, 10 ) . Previous in vivo studies assessing the effect of stretching on the hamstring muscle-tendon complex have demonstrated significant load-relaxation behavior11,12,13 ) . These results indicate that stretching to reduce muscle spasm influences VAS and Oswestry scale scores, as does stretching with lumbar traction.…”
Section: Discussionmentioning
confidence: 99%